Synopsis of the Castniidae (Lepidoptera) of Costa Rica - García-Díaz, José De Jesús; Espinoza-Sanabria, Bernardo A.; Worthy, Robert; González, Jorge M.; Janzen, Daniel H.; Hallwachs, Winnie (Zootaxa, 2024)
Based on an exhaustive review of the bibliography, and consultation of entomological collections around the world, we present an illustrated catalog with 16 Castniidae taxa present in Costa Rica. Corybantes veraguana veraguana (Westwood, 1877) is recorded for the first time in the country and new records are reported for rare and little-known species such as Athis analibiae (Espinoza-Sanabria & González, 2005), Athis delecta (Schaus, 1911) and Mirocastnia pyrrhopygoides smalli Miller, 1980. A taxonomic catalog of each taxon is included, as well as general information on geographic distribution, biogeography, ecology, seasonality, flight habits, material examined, and illustrations of males and females for all those taxa known from more than one specimen from Costa Rica.